When and why might a computer-aided detection (CAD) system interfere with visual search? An eye-tracking study. - Drew T; Cunningham C; Wolfe JM; Drew, Trafton; Cunningham, Corbin; Wolfe, Jeremy M (Academic Radiology, 2012)
Rational and Objectives: Computer-aided detection (CAD) systems are intended to improve performance. This study investigates how CAD might actually interfere with a visual search task. This is a laboratory study with implications for clinical use of CAD.Methods: Forty-seven naive observers in two studies were asked to search for a target, embedded in 1/f(2.4) noise while we monitored their eye movements. For some observers, a CAD system marked 75% of targets and 10% of distractors, whereas other observers completed the study without CAD. In experiment 1, the CAD system's primary function was to tell observers where the target might be. In experiment 2, CAD provided information about target identity.Results: In experiment 1, there was a significant enhancement of observer sensitivity in the presence of CAD (t(22) = 4.74, P < .001), but there was also a substantial cost. Targets that were not marked by the CAD system were missed more frequently than equivalent targets in no-CAD blocks of the experiment (t(22) = 7.02, P < .001). Experiment 2 showed no behavioral benefit from CAD, but also no significant cost on sensitivity to unmarked targets (t(22) = 0.6, P = NS). Finally, in both experiments, CAD produced reliable changes in eye movements: CAD observers examined a lower total percentage of the search area than the no-CAD observers (experiment 1: t(48) = 3.05, P < .005; experiment 2: t(50) = 7.31, P < .001).Conclusions: CAD signals do not combine with observers' unaided performance in a straightforward manner. CAD can engender a sense of certainty that can lead to incomplete search and elevated chances of missing unmarked stimuli.